Getting Started With Collaborative Teamwork for Inclusion - Lawrence-Brown, Diana; Muschaweck, Kim S. (Catholic Education: A Journal of Inquiry and Practice, 2004)
The article illustrates the collaborative team process for inclusion as it grew within two schools attempting to improve their efforts to welcome students with disabilities into general education classrooms. Team members learned specialized skills needed for successful collaboration, in the context of bringing about specific changes they deemed critical to the desired outcomes of their own projects.